Factors Influencing Tourist Satisfaction: An Empirical Study Of Jodhpur As A Tourist Destination (International Journal of Food and Nutritional Sciences, 2022)
The aim of the study is to explore the elements that contribute to visitor satisfaction in Jodhpur as a tourism destination and to examine the degree to which they are interdependent. Data were acquired using a questionnaire from 160 visitors who visited Jodhpur for the purpose of tourism between December 2021 and February 2022. The respondents were selected based on a convenience-based random sampling technique. The demographic profile of the respondents was expressed using descriptive statistics. The researcher has used Multiple regression analysis for the purpose of testing the hypotheses. The finding of the present study indicates that all five components (Natural, Cultural, Support Services, Tourism Products and Financial Factors) were found to be positively related to tourist satisfaction. The findings will aid in improving the performance of government agencies and tourism services, progressively increasing satisfaction among both domestic and foreign travellers. The present research is conducted in a particular part of the country using a convenience-based random sampling technique, so the outcomes cannot be generalised